Hidrodinâmica e transporte de sedimentos em uma área de manguezal na planície costeira de Bragança, Amazônia Oriental – Brasil - MIRANDA, Artur Gustavo Oliveira de (Universidade Federal do Pará, 2019)
The physical processes that occur in intertidal areas are essential for the existence of mangrove ecosystem, due process interaction between oceans and estuaries, with mangroves. The tidal channels represent the most important and peculiar features of coastal environments, due your circulatory system basics which controls both the tidal flow as the channel morphology. This paper presents a set of data to analyze and understand the hydrodynamic process and sediment dynamics in the coastal plain of Bragança, specifically the region known as Furo do Meio tidal channel. At this region were carried out topographic and hydrodynamic collection of data, physicochemical properties of water measurements, surficial sediment collection, and quantification of sedimentation rate according the seasonality pattern (March, July, September and December). As this study demonstrated, the tidal channel presented a well defined bidirectional flow, though the area vegetated by mangrove presented a turbulent flow, so the variation of current speed in both morphological units vary according to seasonality. The average concentration of suspended solids (CSS), between the months from March to September, remained at around 400 ppm in the channel. To the tidal flat dominated by mangrove forest, an average of approximately 21,000 ppm was obtained, while in the month of December, these values were lower than those recorded in previous months, where the maximum CSS in the channel was around 270 ppm and in the mangrove was 1000 ppm. There was not a direct relationship between the CSS and the mangrove channel, where high CSS in the mangrove is associated with the remobilization of the sediment itself at tide input in this area; there was not a significant sedimentary input of mangrove to the channel. Changes in topographical elevation corroborates the values obtained in measurements of trappers and the variation of sedimentary textural classes between fine silt and fine sand are associated with the seasonal hydrodynamic variation.